A Chinese patient of P102L Gerstmann-Sträussler-Scheinker disease contains three other disease-associated mutations in SYNE1. Issue 2 (4th March 2018) - Wang, Jing; Xiao, Kang; Zhou, Wei; Gao, Chen; Chen, Cao; Shi, Qi; Dong, Xiao-Ping
ABSTRACT: Gerstmann-Sträussler-Scheinker disease (GSS) with the P102L mutation in PRNP gene is characterized with progressive cerebellar dysfunction clinically and PrP Sc plaques neurologically. Due to the cerebellar ataxia in the early stage, GSS P102L is often misdiagnosed as other neurodegenerative disorders. We presented here a 49-year-old female patient with proven P102L PRNP mutation, and three heterologous mutations in hereditary ataxias associated gene SYNE1, including p.V3643L, p.M3376V and p.T2860A. The patient appeared progressive unsteady gait in early stage and developed the Creutzfeldt-Jacob disease (CJD) – associated clinical manifestations, including progressive dementia, myoclonus, pyramidal and extrapyramidal signs. She is still alive but with akinetic mutism 21 months after onset. Observation of intense signal changes in cortical regions (cortical ribboning) in diffusion weighted imaging (DWI) MRI scanning and positive protein 14-3-3 in cerebrospinal fluid (CSF) proposed the diagnosis of sporadic CJD. The final diagnosis of P102L GSS was made after PRNP sequencing.